Continuum of Folk to Pop Music in Bangladesh: A Simple Analysis - Hossain Mridha, Md. Anwar; Begum, Monira (Issues in Social Science, 2024)
Folk music is rooted in the heart and acts as the soul of the culture in Bangladesh. It originated when civilization started in this delta land. Different genres of Bangla music originated in different periods, and Bengali music excelled in the hands of Vaishnava masters. There are various evolutions of folk music practice, but it is still alive. Modern (adhunik) music is from nearly a hundred years ago, and band music was from almost four decades ago. Modern Bengali songs have debuted in our musical theater through the hands of lyricists, music composers, singers, and poets from Rabindranath to Nazrul. Bengali songs stand out for their depth of the subject matter, blending of local and foreign tunes, and superior lyrics. Bengali melodies from the past have undergone numerous changes, but they still have their traditional grandeur. Most contemporary music’s themes are based on Bangladeshi life, culture, and beliefs in use today. The tradition, character, breadth, genesis, and demise of Bangla music in Bangladesh are all evaluated in this study article. This essay also outlines Bangladesh’s transition from folk to pop music, concluding with a discussion of contemporary Bangla music issues.